INTUBATING CONDITIONS 60 SECONDS AFTER GIVING MUSCLE RELAXANT FOR RAPID SEQUENCE INDUCTION.COMPARISON BETWEEN SUCCINYLCHOLINE AND ROCURONIUM - Ali, Syed Qasim; Khan, Muhammad Asghar; Yasin, Bilal (Pakistan Armed Forces Medical Journal, 2011)
Objectives: To compare efficacy of Succinylcholine with Rocuronium for rapid sequence induction Study Design: Randomized control trail Place and Duration of Study: The study was done in Anaesthesia department, Combined Military Hospital Kharian from 17th march 2007 to 16th march 2008 Patients and Methods: a total of 100 cases of elective surgery for haemorrhoids were taken and patients were randomly assigned in two equal groups using random number table. American Society of Anesthesiologist (ASA) status was assessed. Informed consent and approval of ethical committee was obtained. Patients were divided into group A and B. In both groups there were 25 males and 25 females of 20-40 years. In group A, patients were preoxygenated for 3 min then propofol was given followed by succinylcholine. After 60 seconds of giving muscle relaxant intubating conditions were assessed by vocal cords movements on laryngoscopy, apnea and abdominal jerky movements on intubation. In group B, rocuronium was given instead of succinylcholine. Results: In group A one (2%) patient was having movement of vocal cords at the time of laryngoscopy while in group B nine (18%) patients had vocal cord movement (p=0.016). As far as apnea is concerned, in group A one (2%) patient was not having apnea after 60 seconds but in group B eight (16%) patients were not having apnea (p=0.031). At the time of intubation in group A three (6%) patients showed jerky movements of abdomen while in group B that movement was present in eleven (22%) patients (p=0.041). Conclusion: Intubating conditions with rocuronium were not superior to those with succinylcholine.